Climate Vulnerability Regarding Heat Waves – A Case Study in Hungary - Annamária Uzzoli; Dániel Szilágyi; Attila Bán (DETUROPE)
One form of climate change vulnerability is the increase in the number, frequency and length of heat waves related to temperature rise. The protection against the health and sanitary risks of heat waves will pose a major challenge at national, regional, as well as local level in the future. The aim of the study is to present the main results of an assessment of climate change vulnerability conducted in a research project. Through statistical analyses, vulnerability was calculated based on the exposure, sensitivity and adaptive capacity at district level (LAU1), which is a complex information carrier about the vulnerability of population and institutions to heat waves. The territorial differences of vulnerability proved the West-East division of the country, but the centre-periphery relation also plays role in the development of territorial pattern. Based on statistical examinations it is ascertainable, that, in total, 42.5% of the country’s territory, where currently 39.5% of the population live, is severe and extreme vulnerable to the effects of climate change. The main results of the research can also be used as suggestions for the local decision-making related to the preparation for and adaptation to the health effects and sanitary consequences of heat waves.